Pengaruh Pelatihan Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Guru di Yayasan AL-Muniroh Ujung Pangkah Gresik - Twovindarista Permatasari Alkusani (Jurnal Pendidikan Islam, 2021)
the purpose of this study to find out The Influence of training, Work motivation, Work environment on teacher performance at the foundation AL-Muniroh Ujung Pangkah Gresik, using saturated sampling method is a sampling technique when all members of the population are used as samples. This is done because the population is too small and the researcher wants to make generalizations with a small error rate of 76 teacher. The data analysis technique used multiple liniear regression analysis. The result showed that training, work motivation, and work environment partially significant influence on the performance of the AL-Muniroh Ujung Pangkah Gresik Foudation teacher.